Galley proof of a report of the Irish National Aid and Volunteer Dependants' Fund - Irish National Aid and Volunteers' Dependants' Fund (1918)
Includes a full history of the administration of the Irish National Aid and Volunteer Dependants' Fund, including outlines of the activities of the Employment Sub-Committee, Civil Service Sub-Committee, Prisoners' Sub-Committee, Ladies (Distribution) Committee and the American Grants Committee.
Includes manuscript annotations.
Keywords: Charities -- Ireland -- Dublin -- 20th Century; Ireland -- History -- 1910-1921; Ireland -- History -- Easter Rising, 1916